The Land Development of Cocoa Plant (Theobroma Cacao L.) Based on Land Suitability Aspect in Sigi Regency, Indonesia - Ramlan, Akram, Salapu Pagiu (International Journal of Advanced Science and Technology, 2020)
This study is aimed to obtain information about the suitability of land use for the development of the agricultural sectorwhich can be used as an input for making land use decisions. Analyzing of soil quality is carried out at the Soil Science Laboratory, Faculty of Agriculture, University of Tadulako. The location of taking soil samples for material analysis in laboratory is determined by the purposive sampling of 8 sample points. The result shows that the land included in the category is quite suitable for the development of cocoa land, namely it is onthe land of 1, 2, 3, 4, 5, 6, 7 and 8 with limiting factors f, n, e, (CEC Soil, Total N, P2O5, K2O , and slopes). After conducting improvement efforts by adding organic material, adding the fertilizer and making terrace so then the land included in the category of potential can be developed as cocoa land, namely, the land of 3, 6 and 7.